2021
DOI: 10.3390/antib11010002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Developability and Disposition Profiles of Bispecific Antibodies: A Case Study with Two Molecules

Abstract: Bispecific antibodies (BsAb) that engage multiple pathways are a promising therapeutic strategy to improve and prolong the efficacy of biologics in complex diseases. In the early stages of discovery, BsAbs often exhibit a broad range of pharmacokinetic (PK) behavior. Optimization of the neonatal Fc receptor (FcRn) interactions and removal of undesirable physiochemical properties have been used to improve the ‘pharmacokinetic developability’ for various monoclonal antibody (mAb) therapeutics, yet there is a spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…L19-IFNγ KRG showed excellent in vivo tumor-targeting properties and modest tumor growth retardation, which was enhanced when the product was used in combination with immune checkpoint inhibitors or with standard chemotherapy. The PK profile in monkeys was similar to the one reported for other IgG-based products [ 47 ]. It would be attractive to use a long-lived product (such as IgGs) to reduce dosing frequency in patients.…”
Section: Discussionsupporting
confidence: 80%
“…L19-IFNγ KRG showed excellent in vivo tumor-targeting properties and modest tumor growth retardation, which was enhanced when the product was used in combination with immune checkpoint inhibitors or with standard chemotherapy. The PK profile in monkeys was similar to the one reported for other IgG-based products [ 47 ]. It would be attractive to use a long-lived product (such as IgGs) to reduce dosing frequency in patients.…”
Section: Discussionsupporting
confidence: 80%
“… 5 , 6 The slow clinical success of BsAbs can be attributed to several factors, including increased structural complexity leading to greater challenges in their CMC properties, and in their pharmacokinetic (PK) profiles. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have aimed to understand the reasons for faster clearance and non-linear PK observed with BsAbs. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Integration of quantitative whole-body biodistribution and tissue level imaging into the development can provide informative readouts regarding the disposition (Boswell et al 2012;Boswell et al 2013;Datta-Mannan 2019;Khawli et al 1996;Khawli et al 2010). Towards this, a handful of imaging approaches including, computed tomography (CT), magnetic resonance imaging, whole-body imaging bioluminescence/radiolabeling and positron emission tomography (PET) have been leveraged (Boswell et al 2013;Datta-Mannan 2019;Datta-Mannan et al 2021;Datta-Mannan A 2016 ;Williams et al 2016;Boswell et al 2019;Datta-Mannan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Like most therapeutics, the causalities of BfAb slow clinical success can be generally related to several factors, including an incomplete understanding of the biologic mechanism of action and exposure–response profiles, insufficient safety margins, strategic industry decisions, and immunogenicity. The higher structural diversity of the BfAbs also results in greater uncertainty in their pharmacokinetic (PK) and disposition profiles that could limit their potential advantages ( Khawli et al, 1996 , 2010 ; Boswell et al, 2012 , 2013 ; Tibbitts et al, 2016 ; Datta-Mannan et al, 2016 , 2019 ; Datta-Mannan et al, 2019 ; Rock and Foti 2019 ; Datta-Mannan et al, 2021 ). As such, consideration of dynamic evaluations of BfAb tissue and cellular biodistribution profiles and how these are connected to their clearance are warranted.…”
Section: Introductionmentioning
confidence: 99%